Investigating the relationship between Kadazandusun beliefs about paddy spirits, riddling in harvest-time and paddy-related sundait - Low, Kok On; Lee, Yok Fee (Universiti Kebangsaan Malaysia, 2012)
During recent field trips to collect sundait (riddles) from Kadazandusun communities in Sabah, it was noted that many of the riddle answers relate to paddy farming: for example, rice planting activities and related paraphernalia are often mentioned. This paper analyzes collected Kadazandusun “paddy- related” sundait based on their social context and background. In addition, it also examines traditional beliefs in paddy spirits and the origin of riddling at harvest-time. Some unique aspects of paddy-related sundait are highlighted and the relationship between the belief in paddy spirits and the ritual of harvest riddling is further explored.